Analisis Kesulitan Membaca Peserta Didik Kelas II SDN 14/1 Sungai Baung - Isratulhasanah, Puji; Marwiyah, Siti; Nurrahmah, Silva; Rizkia, Nadila Putri (Lembaga Yasin AlSys, 2023)
Reading ability is one of the basic language skills. By reading students will apply another ability that is speaking. And also students who are unable to read will find it difficult to fulfill their abilities. Learning to read is the most important part of life, because it is the beginning of our systematic knowledge of the learning process and one of the keys to success in following the process. When learning in class there is interaction in the learning process of teachers and students. Teachers and students are a very important part in determining the success of learning objectives. Reading is a skill that must be taught to children from an early age. If a child of primary school age cannot master early reading skills, he or she will experience many difficulties in learning various subjects in later grades.